2016
DOI: 10.1016/j.ejphar.2016.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antidepressant-like effects between a kappa opioid antagonist (LY2444296) and a delta opioid agonist (ADL5859) in the mouse forced swim test

Abstract: Kappa opioid (KOP) receptor antagonists and delta opioid (DOP) receptor agonists have antidepressant-like effects in animal tests and may be useful for treatment-resistant depression in humans. In this study, we examined whether the combination of a KOP receptor antagonist and a DOP receptor agonist would produce a better than additive effect (i.e. synergy). LY2444296 is a short-acting selective nonpeptide KOP receptor antagonist. ADL5859 is a selective nonpeptide DOP receptor agonist which does not produce se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 42 publications
(62 reference statements)
2
11
0
Order By: Relevance
“…Previous studies showed a reduced latency to immobility and increased open arm exploration induced by long-acting KOPr antagonists, in cocaine naïve rats (Knoll et al 2007; Mague et al 2003; Pliakas et al 2001). In line with our results, two recent studies reported that systemic administration of norBNI, but not 3 mg/kg LY2444296, reduced anxiety-like and depressive-like behaviors in cocaine naïve mice (Huang et al 2016a; Huang et al 2016b). Long-acting KOPr antagonists have complex pharmacokinetics and pharmacodynamic properties.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed a reduced latency to immobility and increased open arm exploration induced by long-acting KOPr antagonists, in cocaine naïve rats (Knoll et al 2007; Mague et al 2003; Pliakas et al 2001). In line with our results, two recent studies reported that systemic administration of norBNI, but not 3 mg/kg LY2444296, reduced anxiety-like and depressive-like behaviors in cocaine naïve mice (Huang et al 2016a; Huang et al 2016b). Long-acting KOPr antagonists have complex pharmacokinetics and pharmacodynamic properties.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the effects of these rapid-acting k-antagonists on immobility in the FST are not due to a simple confound with locomotor function. The rapid effects of compounds from this chemical template in the FST (and of LY2444296) have been observed before (Rorick-Kehn et al, 2014;Huang et al, 2016a). This is the first such examination for LY2795050, to our knowledge.…”
Section: Discussionmentioning
confidence: 64%
“…This is very imperative because as opioid agonists, they induce an analgesic effect, which is characteristically found in opioid ligands, whereas as opioid antagonists at the NK1 receptors, they block the signals induced by the pronociceptive peptides involved in pain signaling . Furthermore, Huang et al (2016) mentioned that the dynorphin/k opioid (KOP) receptor system leads to adverse emotional conditions. When activated by selective agonists, the receptor system causes strong emotional consequences in humans and conditioned place aversion in animals .…”
Section: Opioid and Antinociceptivementioning
confidence: 99%